Mathematical Connections Ability Based on Personality Types in Conceptual Understanding Procedures Model - Nurdiyah, Nurdiyah; Suyitno, Hardi; Junaedi, Iwan (Universitas Negeri Semarang, 2018)
Abst The purposes of this study are to (1) identify learning quality in Conceptual Understanding Procedures (CUPs) model (2) obtain mathematical connections ability based on artisan, guardian, idealist and rational personality types. This research is mixed method concurrent embedded design with qualitative research as the primary method. The type of this research is a quasi-experimental research with one group pretest-posttest design. The subjects in this research consist of 8 students XI RPL grade in SMK N 1 Kabupaten Semarang. Learning quality is assessed from the planning, implementation and evaluation stage. The result of this research shows that CUPs model in good criteria. Mathematical connection ability the artisan personality type reaches several indicators of mathematics connection, but they lack ability in using mathematical operation and can’t apply the concept and procedure relationship which have been given to the new situation. Mathematical connection ability the guardian personality type reaches several indicators of mathematical connections but they are less conscientious in their calculations. Mathematical connection ability of the idealist personality type reaches all indicators of mathematics connections. Mathematical connection ability of the rational personality type reaches all indicators of mathematics connections. rak ___________________________________________________________________ Penelitian ini bertujuan untuk (1) medeskripsikan kualitas pembelajaran pada model CUPs (2) menemukan pola kemampuan koneksi matematik ditinjau dari tipe kepribadian. Penelitian ini menggunakan jenis penelitian mixed method dengan desain concurrent embedded design. Penelitian kuantitatif dan penelitian kualitatif berjalan beriringan dimana penelitian kualitatif sebagai metode primer. Jenis penelitian kuantitatif yang digunakankan adalah penelitian eksperimen dengan Nonrandomized Control Group. Kualitas pembelajaran kualitatif dinilai dari tahap perencanaan, pelaksanaan, dan penilaian. Hasil penelitian menunjukkan bahwa pembelajaran model CUPs berkualitas dalam kategori baik. Hasil validasi ahli pada tahap perencanaan, observasi keterlaksanaan pembelajaran pada tahap pelaksanaan dan hasil angket respon pada tahap penilaian masuk ke dalam kriteria minimal baik. Siswa dengan pembelajaran model CUPs mencapai ketuntasan belajar dan rata-rata kemampuan koneksi matematik siswa setelah dikenai pembelajaran CUPs lebih baik daripada rata-rata kemampuan koneksi matematik sebelum dikenai pembelajaran CUPs. Siswa dengan tipe kepribadian artisan sudah mencapai beberapa indikator kemampuan koneksi matematik, namun kurang lancar dalam menggunakan menggunakan operasi matematika serta belum dapat menerapkan hubungan konsep dan prosedur yang telah diberikan pada siatuasi baru. Siswa dengan tipe kepribadian guardian sudah mencapai beberapa indikator kemampuan koneksi matematik tetapi kurang teliti pada perhitungannya. Siswa dengan tipe kepribadian idealist sudah mencapai semua indikator kemampuan koneksi matematik. Siswa dengan tipe kepribadian rational sudah mencapai semua indikator kemampuan koneksi matematik. Abstract __________________________________________________________________ This study aims to: (1) determine the quality of the CUPs model qualitatively and quantitatively, (2) found a pattern of mathematics connections ability of students of class XI viewed by personality types. This study used mixed method with concurrent embedded design, which qualitative as a primary method. The design of quantitative research was quasi experimental with nonequivalent control group design. The subject of this study were 11th grader students of SMK N 1, Kab Semarang. The quality of learning qualitatively assessed from the planning and preparation, implementation, and assessment. The quality of learning quantitatively was analyze using paired t-test and z-test.The resul ts showed that the learning by using CUPs model qualified both qualitatively and quantitativly. Students with artistic personality types have achieved some indicators of mathematics connection ability, but are less fluent in using mathematical operations and have not been able to apply the conceptual relationships and procedures that have been assigned to a new situation. Students with guardian personality types have already achieved some indicators of mathematics connection capabilities but are less conscientious in their calculations. Students with idealist personality types have achieved all indicators of mathematical connection capability. Students with rational personality types have reached all indicators of mathematical connection ability. © 2017 Universitas Negeri Semarang